(3ef dG jMVQg Gdabjgs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs
(3ChdgG (B:s
(3HSe Gddg (B.. (3CHhGH GdbVGjG hGdCMcGe ; HGH ef jLhR GdJMGce Edjg hef dG jLhR (B.. (3Qhi CMeO Hf YGFO Yf CHj NOjLI SGde Hf ecQe GdLqeGd bGd bGd CHh YHO Gddg LYaQ Hf eMeO GdUGOb Ydjg GdSdGe (B...s
(3BNQgG (B:s
... (3heG ajg ef hUjI CejQ GdeDefjf Ydjg GdSdGe dGHfg eMeO Hf GdMfjajI aef eQGSjd MeGO Hf YjSi GdKbI CQSdg Yf CHj YHO Gddg Ydjg GdSdGe hGdWQjb Edjg MSf HEHQGgje Hf gGTef (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\ 274s
22\6841
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs